Novidades no âmbito da epigrafia pré-romana do sudoeste hispânico (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This contribution presents some recent Tartessian inscriptions from the south Portugal, especially an important epigraphy, from the southern area of the Alentejo. The monument was identified during the excavations at Mesas do Castelinho in an archaeological context of the Roman republican period, in a layer from the end of the 2th century BC. The inscribed stone reveals, in acceptable conditions in almost all its extension, the longest text so far known, with more than 80 characters, which is very important to the research on a domain where large and well preserved sequences are lacking. A new stela found at the end of 2008 in Corte Pinheiro (Loulé) and discovered within the Project ESTELA will be also analyzed. Finally, we review a recently published inscription from Vale de Águia (Silves).
Keywords: Iron Age; Tartessian inscriptions; Southwestern Iberia inscribed stellae; Mesas do Castelinho (Almodôvar, Portugal); Corte Pinheiro (Loulé, Portugal)